2022
DOI: 10.15406/aovs.2022.12.00410
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about retinopathy of prematurity among nurses working at neonatal intensive care unit of nampula central hospital in mozambique, 2021

Abstract: Introduction: Retinopathy of prematurity is a bilateral dysfunction of abnormal retinal vascularization in preterm infants, especially those with very low birth weight. The consequences range from normal vision to blindness. In recent years, the survival rate for the extreme group of patients with prematurity has increased from 8% to 35% in middle-income countries, as well as its early identification of retinal damage and institution of appropriate treatment to prevent blindness and provide children with bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous studies have reported a 33-73% incidence of ROP (at any stage) in preterm infants less than 27-28 weeks and severe ROP in 16-35% [9][10][11][12][13]. Awareness and knowledge of ROP may be given to all healthcare providers, including nurses [14,15]. All hospitals that provide neonatal care should have a protocol for screening and management of ROP and a protocol for training new neonatologists.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a 33-73% incidence of ROP (at any stage) in preterm infants less than 27-28 weeks and severe ROP in 16-35% [9][10][11][12][13]. Awareness and knowledge of ROP may be given to all healthcare providers, including nurses [14,15]. All hospitals that provide neonatal care should have a protocol for screening and management of ROP and a protocol for training new neonatologists.…”
Section: Discussionmentioning
confidence: 99%